Eksternalisasi Kompetensi Guru Terhadap Akhlak Peserta Didik - Sumiati, Cucu; Dr, Wawan; Juanda, Ayi (Prodi PAI IAILM Suryalaya, 2024)
This study aims to analyze and explain how the effect of Islamic Religious education teacher competence on Student Morals. The type of research used in this research is quantitative research, all actions taken are an effort to find out and measure